Metatranscriptome of an Anaerobic Benzene-Degrading, Nitrate-Reducing Enrichment Culture Reveals Involvement of Carboxylation in Benzene Ring Activation - Luo, Fei (American Society for Microbiology, 2014)
The enzymes involved in the initial steps of anaerobic benzene catabolism are not known. To try to elucidate this critical step, a metatranscriptomic analysis was conducted to compare the genes transcribed during the metabolism of benzene and benzoate by an anaerobic benzene-degrading, nitrate-reducing enrichment culture. RNA was extracted from the mixed culture and sequenced without prior mRNA enrichment, allowing simultaneous examination of the active community composition and the differential gene expression between the two treatments. Ribosomal and mRNA sequences attributed to a member of the family Peptococcaceae from the order Clostridiales were essentially only detected in the benzene-amended culture samples, implicating this group in the initial catabolism of benzene. Genes similar to each of two subunits of a proposed benzene-carboxylating enzyme were transcribed when the culture was amended with benzene. Anaerobic benzoate degradation genes from strict anaerobes were transcribed only when the culture was amended with benzene. Genes for other benzoate catabolic enzymes and for nitrate respiration were transcribed in both samples, with those attributed to an Azoarcus species being most abundant. These findings indicate that the mineralization of benzene starts with its activation by a strict anaerobe belonging to the Peptococcaceae, involving a carboxylation step to form benzoate. These data confirm the previously hypothesized syntrophic association between a benzene-degrading Peptococcaceae strain and a benzoate-degrading denitrifying Azoarcus strain for the complete catabolism of benzene with nitrate as the terminal electron acceptor.